The effect of intermittent hypoxic training via a hypoxic inhaler on physiological and performance measures in rowers: A pilot study - Hinckson, E. A.; Hopkins, W. G.; Downey, B. M.; Smith, T. B. R. J (Journal of Science and Medicine in Sport, 2006)
Intermittent hypoxic training and discontinuous exposure to altitude were used to improve performance at sea level in elite rowers. Altitude was simulated with a newly patented device which allowed athletes to experience altitude by re-breathing oxygen-depleted expired air. Seven elite rowers (five females, two males) used inhalers for a 90-min supervised daily session (alternating 6 min on and 4 min off) for 3 weeks, while four female elite rowers used placebo devices in the same sessions. The inhalers were adjusted to produce a progressive decrease in oxygen saturation over the 3 weeks (initially 90%; finally 80%). Immediately before and 7-10 days after altitude exposure, the rowers performed an incremental lactate test to determine power output equivalent to 4 mM [BLa], a 500-m time trial and a 5000-m time trial, all on a rowing ergometer. Relative to the control group, the altitude group showed a slight improvement in mean power for the 5000-m time trial (0.6%, 90% likely limits ±3.7%), and a substantial impairment in mean power for the 500-m trial (2.2%, ±4.1%). Power at 4-mM lactate declined in both groups, but overall the altitude group improved by 0.4% (±3.5%) relative to control. The device represents a practical way to simulate altitude exposure, but it is unlikely to have major effects on performance of elite rowers.